2020
DOI: 10.18203/2349-3933.ijam20205045
|View full text |Cite
|
Sign up to set email alerts
|

Study of hematological and biochemical parameters in a cohort of Indian COVID-19 patients admitted in a tertiary care centre

Abstract: Background: In this study authors retrospectively analyzed the record of 102 patients with confirmed COVID-19 infection to determine factors associated with severity of disease.  Methods: Clinical, biochemical, radiological and hematological profiles of 102 patients with confirmed SARS-CoV-2 RNA testing were obtained and analyzed.  Results: A total of 102 patients were enrolled, with median age of patients of 32.5 years (range 10-85 years), of which 83.3% (85/102) were asymptomatic and 16.67% (17/102) symptoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
(14 reference statements)
2
8
0
Order By: Relevance
“…In a study by Forget P et al, 21 it was identified that normal NLR values in an adult, non-geriatric and population in good health, are between 0.78 and 3.53. In our study significant difference was seen in levels NLR of severe cases as compared to non severe cases, This is concordant with studies done by Archana B et al 10 (Non survivors 8.40 vs survivors 2.95, p=0.04),and Agrawal A et al 8 (symptomatic cases 6.17±6.11 and in asymptomatic was 2.67±1.32, p value 0.0001).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In a study by Forget P et al, 21 it was identified that normal NLR values in an adult, non-geriatric and population in good health, are between 0.78 and 3.53. In our study significant difference was seen in levels NLR of severe cases as compared to non severe cases, This is concordant with studies done by Archana B et al 10 (Non survivors 8.40 vs survivors 2.95, p=0.04),and Agrawal A et al 8 (symptomatic cases 6.17±6.11 and in asymptomatic was 2.67±1.32, p value 0.0001).…”
Section: Discussionsupporting
confidence: 92%
“…In our study significant higher levels of AST were seen in severe cases as compared to non severe cases; while no association was seen in levels of ALT. In a study of Agrawal A et al 8 showed mean AST values were significantly higher in symptomatic patients (AST (U/l) 30.62±23.98) as compared to asymptomatic patients 66.06±59.68 (p values <0.0001) and ALT values were (U/l) 37.02±36.53 in symptomatic patients and 68.71±52.94 in asymptomatic patients with p value 0.003. Guan Y et al 31 observed that 18.2% patients with non-severe disease and 39.4% patients with severe disease had elevated AST level, whereas elevated ALT levels were observed in 19.8% of patients with non-severe disease and 28.1% of patients with severe disease.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In the studies done by Guan et al 10 , Huang et al 11 , Young et al 14 , Fan et al 15 , Zhou et al 17 , Liu et al 21 and Chen et al 22 hemoglobin concentration (gm%) were 13.4, 12.6, 13.5, 14.2, 12.8, 12.8 gm and 14.8 respectively. In a study by Agrawal A et al 40 hemoglobin concentration (gm%) was 13.85 & 13.12 in asymptomatic and symptomatic patients respectively. In the present study HB concentration was 11.85 gm% (range: 8.2-15.5).…”
Section: Discussionmentioning
confidence: 91%
“…Both studies showed a male predominance (82.1% and 70%). 18,19 Two studies from India by Anurag A et al 39 and Agrawal A et al 40 comprised of 148 and 102 confirmed cases of COVID-19. The age in these studies ranged from 7-74 years (median 42.6 years) and 10-85 years (median 32.5 years).…”
Section: Discussionmentioning
confidence: 99%